2007
DOI: 10.1016/j.ymeth.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-flow fluorescence resonance energy transfer for analysis of nucleosome dynamics

Abstract: Macromolecular assemblies and machines undergo large-scale conformational changes as essential features of their normal function. Modern stopped-flow instrumentation and biotechnology combine to provide a powerful tool for characterizing the rates and natures of these conformational changes. Standard commercially available instruments provide extraordinary sensitivity and speed, allowing analysis of millisecond or longer timescale processes, with concentrations as low as a few nanomolar and volumes of just a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…This suggests that DNA breathing may only marginally increase accessibility to occluded uracils by capturing the transient exposed states. This is not surprising given that only 1-10% of the time occluded sites are exposed through this mechanism (61). This is in agreement with the findings reported previously on the effects of rotational and translational positioning on uracil removal efficiency (32).…”
Section: A Andsupporting
confidence: 92%
“…This suggests that DNA breathing may only marginally increase accessibility to occluded uracils by capturing the transient exposed states. This is not surprising given that only 1-10% of the time occluded sites are exposed through this mechanism (61). This is in agreement with the findings reported previously on the effects of rotational and translational positioning on uracil removal efficiency (32).…”
Section: A Andsupporting
confidence: 92%
“…This time scale is very close to that of unwrapping-rewrapping event observed in single-molecule FRET experiments [23,24]. It has been shown that wrapping-unwrapping of DNA is an intrinsic property of nucleosome, and, nucleosomes are partially unwrapped about 2-10% of the time [23].…”
Section: Nucleosome Movement Along the Dnasupporting
confidence: 78%
“…Single-molecule measurement using optical trap has shown that the wrapping and unwrapping of DNA between 1 and 1.75 turns occur reversibly [21,22]. Single-molecule fluorescence resonance energy transfer (FRET) techniques have detected a local dissociation of DNA from histone core particle occurring in sub-second time scale [23,24]. These investigations indicate that thermal fluctuation is possibly responsible for the nucleosome dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was shown that differences in NCP stability occur in DNA positioning sequences around promoter regions of Mouse Mammary Tumor Virus, where the nucleosome at the promoter is inherently more dynamic/unstable compared to another nucleosome nearby, possibly for targeting transcriptional activators (35). Additionally, DNA sequence plays an important role in regulating transient dynamic states of DNA on the surface of the histone octamer in which the DNA transiently lifts off the surface of the histone octamer to allow regulatory proteins access to buried target sites (36-38). Although these ‘site exposure’ or ‘DNA unwrapping’ events were originally considered to occur only in vitro , in vivo results also point to the existence of such a mechanism.…”
Section: Factors Influencing Dna Accessibility In Chromatin At Thementioning
confidence: 99%